Unexpected flavors: development of crackers with nonconventional food plants as calcium source using experimental design - NAKAJIMA, Vânia Mayumi; SILVA, Isabele de Souza Paula; PEREIRA, João Pablo Fortes; POLICARPO, Nathália Lage; MARTINS, Marcos Vidal; SOUSA, Rafael Arromba de (Food Science and Technology, 2024)
Alternative calcium sources, such as nonconventional food plants, are essential for those who avoid dairy. However, consuming plant-based calcium with meals may compete for iron absorption. The aim of this study was to identify potential calcium sources among these plants and develop a plant-based cracker. Amaranthus viridis, Anredera cordifolia, Lactuca canadensis, Pereskia aculeata, Portulaca oleracea, and Stachys byzantine were studied. After flour was produced, proximate composition and calcium and phytate content were determined. The cracker formulations were defined using the Plackett–Burman design, followed by the Central Composite Rotatable Design, and the acceptance score was the response variable (p ≤ 1%). All samples had high calcium content, above 1,000 mg.100 g-1 of flour. Considering the phytate:calcium ratio, P. aculeata was selected for cracker preparation. In the first design, the significant variables were vegetable flour and coconut oil. These ingredients varied in the second design, in which the proposed model was significant but did not have a satisfactory R-value (12.60%), probably due to the lack of discrimination between the samples. However, in the second design, the average scores increased (first = 4.1 and second = 5.6), indicating that acceptance was better. In conclusion, P. aculeata is a potential calcium source and can be incorporated into other preparations, beyond traditional salads.